Hand injuries in a human caused by a South American porcupine (ouriço-cacheiro) - Haddad, Jr. [UNESP]; Vieira, R. B. [UNESP]; Cortes, C. R. (FapUNIFESP (SciELO), 2010)
Human injuries caused by South American porcupines (in Portuguese, ouriço-cacheiro) are rare. This study reports severe hand injuries provoked by the body spines of the animal in a human and discusses the circumstances involved in the accident, with emphasis on environmental factors.
Keywords: Body spines; Brazil; Hand injuries; South American porcupine